2001
DOI: 10.1159/000050787
|View full text |Cite
|
Sign up to set email alerts
|

An Atypical Neuropsychological Profile of a Korsakoff Syndrome Patient throughout the Follow-Up

Abstract: The basis of amnesia in alcoholic Wernicke-Korsakoff syndrome (WKS) has been generally associated with diencephalic lesions and more specifically with lesions of the anterior thalamic nuclei. These brain structures are considered to be involved in encoding/consolidation processes of episodic memory. However, frontal lobe damage responsible for executive function deficits has also been documented. The present report details the nature and extent of amnesia in an alcoholic patients with WKS and which appears to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…Executive functions are often impaired in KS, likely reflecting frontal system dysfunction associated with KS and chronic alcoholism in general (Brand et al, 2005; Brokate et al, 2003; Jacobson et al, 1990; Kopelman, 1995b; Noel et al, 2001; Oscar-Berman et al, 2004; Shimamura et al, 1988). Frontal lobe dysfunction in KS amnesia can affect component processes such as attention, working memory, retrieval strategies, and organization, all of which can play a role in anterograde episodic memory function or even masquerade as an anterograde episodic memory deficit itself (Oscar-Berman, 2012).…”
Section: Cognitive Correlates Of Anterograde Memory Processes In Ksmentioning
confidence: 99%
“…Executive functions are often impaired in KS, likely reflecting frontal system dysfunction associated with KS and chronic alcoholism in general (Brand et al, 2005; Brokate et al, 2003; Jacobson et al, 1990; Kopelman, 1995b; Noel et al, 2001; Oscar-Berman et al, 2004; Shimamura et al, 1988). Frontal lobe dysfunction in KS amnesia can affect component processes such as attention, working memory, retrieval strategies, and organization, all of which can play a role in anterograde episodic memory function or even masquerade as an anterograde episodic memory deficit itself (Oscar-Berman, 2012).…”
Section: Cognitive Correlates Of Anterograde Memory Processes In Ksmentioning
confidence: 99%
“…The Hayling task has frequently been used to explore inhibition abilities in various psychopathological and neuropsychological conditions such as schizophrenia (Marczewski et al, 2001), alcoholism (Noël et al, 2001), Tourette's syndrome (Channon et al, 2004), focal frontal lesions (Burgess & Shallice, 1996;Andrés & Van der Linden, 2001), Alzheimer's disease (Collette et al, 1999), and Parkinson's disease (Bouquet et al, 2003). In addition, it has been shown that inhibition deficits, as assessed by the Hayling task, are related to problems maintaining short-term abstinence from alcohol (Noël et al, 2002) and to auditory hallucinations in schizophrenia (Waters et al, 2003). However, besides response inhibition abilities, it appears the Hayling task also requires the ability to strategically generate nonstereotypical responses; these two capacities stand in a necessary reciprocal causal relationship and are therefore difficult to distinguish (Burgess & Shallice, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Impairments in executive cognitive performance related to dysfunction of the frontal lobes have been well documented in chronic heavy drinkers and alcoholics (Cargiulo, 2007;Kokavec & Crowe, 1999;Lyvers, 2000;Noel et al, 2001;Sullivan, Rosenbloom & Pfefferbaum, 2000). Although alcoholics have been shown as a group to exhibit impaired executive cognitive functioning compared to non-alcoholic controls, such results do not necessarily tell us whether the deficits preceded the alcoholism or whether all such deficits emerged as a result of chronic exposure to neurotoxic effects of alcohol.…”
mentioning
confidence: 99%